Social-emotional learning through STEAM projects, grades 4-5 - Mussey, Season S. (New York, NY Routledge, Taylor & Francis Group, 2022)
Social-Emotional Learning Through STEAM Projects, Grades 4-5 helps educators target the development of social and emotional learning (SEL) competencies for high-ability learners through interdisciplinary, project-based inquiry. Aligned with STEAM content standards, each of the nine projects introduces students to a real-world problem through essential questions and the presentation of a primary source document. Both the content and inquiry process support SEL competencies, from self-awareness to self-management, social awareness, relationship skills, and responsible decision making. As students work to understand and pose solutions to each problem, they gain the knowledge and practical skills needed to become more socially and emotionally competent individuals in their classroom communities"--
Teachers' guide to social-emotional learning through STEAM projects -- Humans and the environment -- Humans and health -- Technology and society.
Includes bibliographical references.
Keywords: Affective education; Social learning; Arts -- Study and teaching (Elementary) -- Social aspects; Science -- Study and teaching (Elementary) -- Social aspects